Prognostic value of procalcitonin in acute exacerbation of chronic obstructive pulmonary disease: A systematic review and meta-analysis. - Pang Qiyuan; Lin Changyang; Li Gaigai; Qiu Ju; Zhou Xun (PLoS ONE)
Aims To evaluate the prognostic role of procalcitonin(PCT) on all-cause mortality in acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Methods Database including PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials were searched to find relevant trials. We included studies with patients hospitalized for AECOPD, which assessed procalcitonin levels and reported on the association between procalcitonin and mortality.. Results Fourteen trials involving 2983 patients were included. We found PCT levels in patients hospitalized for AECOPD are not associated with increased risk of mortality (RR 1.03, 95%CI 0.99-1.08). However, subgroup analysis showed PCT levels are indeed associated with an increased risk of mortality in mild to moderate AECOPD(RR 1.74, 95%CI 1.11-2.73). Deceased patients had significantly higher PCT levels, compared to survivors (MD 0.61, 95%CI 0.30-0.92). In PCT positive group, there was a significant increase in all-cause mortality(OR 3.21, 95%CI 1.84-5.61). Conclusions Results from this meta-analysis suggest that procalcitonin levels at the time of hospital admission for mild to moderate AECOPD are positively correlated with mortality.